2017
DOI: 10.1016/j.brainresbull.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and antihyperalgesic properties of the novel α2/3 preferring GABA A receptor ligand MP-III-024

Abstract: γ-aminobutyric acid type A (GABAA) receptors are located in spinal nociceptive circuits where they mediate the transmission of pain sensory signals from the periphery to higher centers. Benzodiazepine-type drugs bind GABAA, receptors containing α1, α2, α3, and α5 subunits (α1GABAA, α2GABAA, α3GABAA, and α5GABAA receptors, respectively) through which they inhibit the transmission of these signals. However, the role of these different GABAA receptor subtypes in the antihyperalgisic properties of benzodiazepine-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
2
24
1
Order By: Relevance
“…13). MP-III-024 and KRM-II-81 exhibited significant antinociceptive effects (Fischer et al, 2017;Lewter et al, 2017). HZ166 produced some anticonvulsive (Rivas et al, 2009), anxiolytic-like (Savi c et al, 2010), and antihyperalgesic effects (Di Lio et al, 2011), while it was devoid of sedation and motor impairment in rodents in some (Rivas et al, 2009;Di Lio et al, 2011), but not all, studies (Savi c et al, 2010).…”
Section: Compounds Claimed To Selectively Modulate A2bg2 and A3bg2mentioning
confidence: 98%
See 2 more Smart Citations
“…13). MP-III-024 and KRM-II-81 exhibited significant antinociceptive effects (Fischer et al, 2017;Lewter et al, 2017). HZ166 produced some anticonvulsive (Rivas et al, 2009), anxiolytic-like (Savi c et al, 2010), and antihyperalgesic effects (Di Lio et al, 2011), while it was devoid of sedation and motor impairment in rodents in some (Rivas et al, 2009;Di Lio et al, 2011), but not all, studies (Savi c et al, 2010).…”
Section: Compounds Claimed To Selectively Modulate A2bg2 and A3bg2mentioning
confidence: 98%
“…KRM-II-81, a derivative of HZ166 carrying an oxazole ring instead of the ethyl ester of HZ166, exhibited a higher potency and efficacy for a2b3g2 and a3b3g2 receptors (Lewter et al, 2017). However, the respective concentration-response curves indicate that all three of these compounds already at 100 nM concentrations significantly modulate a1 and a5 receptors in addition to a2/a3 receptors (Rivas et al, 2009;Fischer et al, 2010Fischer et al, , 2017Lewter et al, 2017) (Fig. 13).…”
Section: Compounds Claimed To Selectively Modulate A2bg2 and A3bg2mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo proof of concept demonstrated that, in contrast to HZ-166, KRM-II-81 prevented the suppression of responding of rats in a Vogel conflict test (Poe et al, 2016), a result extended to other molecules in this series (Witkin et al, 2017) and thus demonstrating anxiolytic-like activity in this rodent model. This in vivo translation has been also extended with these molecules into the pain domain (Lewter et al, 2017;Fischer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…HZ166 did not generate neither locomotor impairment, sedation, nor tolerance (Di Lio et al, 2011). A newer BDZ-type drug, MP-III-024, is a a2/a3GABA A R PAM that displayed analgesic effects in inflamed mice without significant effects on the open field performance (Fischer et al, 2017). In the same line, KRM-II-81 is another a2/a3-selective GABA A R BDZsite ligand that displayed anti-nociceptive effects in rodents with reduced motor side effects (Lewter et al, 2017;Witkin et al, 2019).…”
Section: Gaba a Rsmentioning
confidence: 99%